Analisis Retorika dalam Tafsir Shafwah Al-Tafasir Terhadap Surah Al-Bayyinah - Fuad Salim; Abuzar Alghifari; Beko Hendro (Universitas Islam Tribakti Lirboyo Kediri, 2024)
One of the main characteristics of the Qur'an is its captivating and impactful language that communicates its messages deeply to the listeners' souls. To explore and elucidate this dimension, scholars utilize a discipline known as the Science of Rhetoric (Ilmu Balaghah). Therefore, the author is interested in exploring the message of Surah Al-Bayyinah through the lens of Ilmu Balaghah to uncover the beauty and depth of meaning it contains. Consequently, this research will focus on two aspects: firstly, identifying the rhetorical styles present in Surah Al-Bayyinah; secondly, examining the implications of employing rhetorical styles in interpreting Surah Al-Bayyinah. Furthermore, this study is a literature review (library research) using a qualitative method. The research findings indicate that: 1) Surah Al-Bayyinah contains various rhetorical styles. Ash-Shabuni in his book